Multivariate analysis of prognostic factors in primary squamous cell vulvar cancer: The role of perineural invasion in recurrence and survival. Issue 11 (November 2019) - Ferrari, Federico; Forte, Sara; Ardighieri, Laura; Bonetti, Emma; Fernando, Barbera; Sartori, Enrico; Odicino, Franco
Abstract: Objective: to assess the prognostic role in recurrence and survival of perineural invasion (PNI) in vulvar squamous cell cancer (VSCC). Methods: Patients underwent primary surgery for VSCC from January 2009 to December 2016 served as the study cohort. We collected demographic, clinical, pathological characteristics and follow-up data, and we compared them among PNI-negative versus -positivepatients. We calculated disease-free survival (DFS) and overall survival (OS) using Kaplan-Meier and univariate log-rank test. We conducted a multivariate analysis with cox-proportional hazard models for DFS and OS, including age, tumor size, depth of invasion, free tumor margin <8 mm, high-grade histology, lymph vascular space invasion, PNI, extracapsular lymph nodal disease, lymph nodal ratio >0.2 and FIGO Stage 2009 (Early I-II versus Advanced III-IV). Results: We found 74 patients with a PNI prevalence of 31.1%. The 5-year DFS was favourable for PNI-negative patients (72% versus 18%; p = 0.00). The 5-year OS was 75% versus 35% in favor of PNI-negative patients (p = 0.00). The subgroup analysis conducted among stage confirmed a decreased DFS and OS in PNI-positive patients. Multivariate analysis showed that PNI (HR 2.74; CI95% 1.10–7.13; p = 0.03) and extracapsular lymph nodal disease (HR 13.54; CI95% 2.87–64.07; p = 0.01) are independent prognostic factors for earlier recurrence. OS was significantly reduced in case of PNI (HR 4.93; CI95% 1.33–18.35; p = 0.01) and extracapsular lymph nodal disease (HR 10.63; CI95% 1.65–68.57; p = 0.01). Conclusions: PNI is an independent prognostic factor for aggressive behavior and unfavorable course in VSCC and should be considered in adjuvant treatment planning.